Hypoparathyroidism Causing Seizures: When Epilepsy Does Not Fit - Faheem Seedat; Reyna Daya; Sindeep A. Bhana (Case Reports in Medicine)
A 24-year-old man presented to the Chris Hani Baragwanath Academic Hospital emergency department with recurrent seizures having previously been diagnosed with epilepsy from age 14. The biochemical investigations and brain imaging were suggestive of seizures secondary to hypocalcemia, and a diagnosis of idiopathic hypoparathyroidism was confirmed. After calcium and vitamin D replacement, the patient recovered well and is seizure free, and off antiepileptic therapy. This case highlights the occurrence of brain calcinosis in idiopathic hypoparathyroidism; the occurrence of acute symptomatic seizures due to provoking factors other than epilepsy; and the importance, in the correct clinical setting, of considering alternative, and sometimes treatable, causes of seizures other than epilepsy.